IMPLIKASI KEPPRES NO.12 TAHUN 2020 PADA PERUSAHAAN PEMBIAYAAN - Marhaeni Ria Siombo; Emmanuel Ariananto Waluyo Adi (Universitas Kristen Satya Wacana, 2020)
The agreement contains the rights and obligations of the parties in carrying out their respective achievements, if they do not make an achievement then it is considered to have committed default. But there is an excuse as regulated in article 1245 of the Civil Code. The Covid-19 outbreak is designated as a non-natural national disaster (Presidential Decree No.12 of 2020), has a very broad impact including the scope of financing companies which resulted in many debtors experiencing defaults. Presidential Decree No.12 of 2020 is very relevant to article 1244 and article 1245 of the Civil Code. Therefore it is not a category of default. However, good faith (Article 1338 paragraph 3) and the principle of appropriateness (Article 1339) of the Civil Code must underlie the application of Article 1245. The impact of the stipulation of Presidential Decree No. 12 of 2020 is that debtors who failed to pay should receive relaxation, payment relief by exempting from interest payment, as stated in Article 1245 of the Civil Code.